Carbon monoxide (CO)-Strengthened cooperative bioreductive anti-tumor therapy via mitochondrial exhaustion and hypoxia induction. (July 2019) - Li, Yongjuan; Dang, Juanjuan; Liang, Qiujun; Yin, Lichen
Abstract: Bioreductive chemodrugs require hypoxic conditions to activate their anti-cancer efficacy. The insufficient and heterogeneous hypoxic condition in tumor tissues hurdles the therapeutic potency of bioreductive chemodrugs. We herein report a NIR light-triggered CO release system based on mesoporous Prussian blue nanoparticles (PB NPs) to enable cancer-selective hypoxia aggravation and hypoxia-responsive activation of bioreductive anti-cancer drug, tirapazamine (TPZ). Pentacarbonyl iron (Fe(CO)5 ) was coupled to PB NPs via coordination interaction, and TPZ was encapsulated into the pores of PB NPs. To prolong blood circulation and improve tumor accumulation, the PB-CO-TPZ NPs were surface-decorated with PEG-NH2 . Upon tumor site-specific light irradiation, the non-lethal photothermal effect of PB NPs released CO, which accelerated mitochondrial oxygen consumption and generated hypoxia to activate TPZ. The CO-induced mitochondrial exhaustion simultaneously led to cancer cell apoptosis, thus realizing synergistic anti-cancer effect with TPZ-mediated bioreductive chemotherapy. To the best of our knowledge, it is the first time to activate bioreductive chemotherapy using CO. This study thus provides a promising paradigm to realize effective and safe cancer treatment via precise manipulation of drug activities, and may open new insights in the use of CO for biomedical treatment.